Analisis Pengaruh Non Performing Loan (NPL) terhadap Profitabilitas pada PT Bank Rakyat Indonesia (Persero) Tbk Tahun 2021-2025 - Ahmad Ubaidilah Yahya; Ferdika Setiadi Kurniawan; Iqbal Ade Saputra; Iqsan Dinata; Fikri Rizki Utama (Indo Publishing, 2026)
This study aims to analyze the effect of Non-Performing Loan (NPL) on profitability at PT Bank Rakyat Indonesia (Persero) Tbk during the 2021–2025 period. Profitability in this study is proxied by Return on Assets (ROA). The research uses a quantitative approach with a causal associative method. The data used are secondary data obtained from the annual financial reports of PT Bank Rakyat Indonesia (Persero) Tbk. Data analysis was conducted using simple linear regression analysis with the assistance of SPSS software. The results of the study indicate that NPL has a negative relationship with ROA, with a regression coefficient value of -0.585. This means that an increase in NPL tends to reduce the bank’s profitability. However, the t-test results show that NPL does not have a significant effect on ROA, with a significance value of 0.795 > 0.05. In addition, the coefficient of determination (R²) result of 0.026 indicates that NPL is only able to explain 2.6% of the variation in ROA, while the remaining 97.4% is influenced by other factors outside this study. Thus, although NPL has a negative relationship with profitability, its effect is not statistically significant at PT Bank Rakyat Indonesia (Persero) Tbk during the 2021–2025 period.